PELATIHAN MANAJEMEN PRODUKSI KONTEN EDUKASI BERBASIS VIDEO BAGI GURU DAN SISWA SMA NEGERI DI KABUPATEN BOGOR - Kirana, Anindya Puspa; Ima; Soeganda, Bintang Caraka (SAHID MENGABDI: Jurnal Pengabdian Masyarakat Institut Agama Islam Sahid Bogor, 2025)
The video-based educational content production management training for teachers and students at public senior high schools in Bogor Regency aimed to enhance technical skills, pedagogical understanding, and digital media literacy. This study employed a participatory method with a hands-on training approach, involving 40 participants (15 teachers and 25 students). Data were collected through observation, questionnaires, and video product analysis, and analyzed qualitatively using descriptive techniques. The results showed significant improvement in pre-production, production, and post-production skills, particularly in visual creativity, image quality, and storyline coherence. Although audio quality remained a challenge, participant enthusiasm was high, with 95% actively engaged in every stage. The training also shifted teachers’ perceptions of video production from a complex process to a skill that can be integrated into teaching. This activity has implications for developing a replicable training model in other regions to foster a creative and adaptive digital learning ecosystem.